Small molecule inhibitor targeting the Hsp70-Bim protein–protein interaction in estrogen receptor-positive breast cancer overcomes tamoxifen resistance - Ting Song; Hong Zhang; Qicheng Zhao; Zhiyuan Hu; Ziqian Wang; Yang Song; Zhichao Zhang (Breast Cancer Research, 2024)
Abstract Introduction Estrogen receptor (ER) positive patients compromise about 70% of breast cancers. Tamoxifen, an antagonist of ERα66 (the classic ER), is the most effective and the standard first-line drug. However, its efficacy is limited by the development of acquired resistance. Methods A specific inhibitor of Hsp70-Bim protein–protein interaction (PPI), S1g-2, together with an inhibitor of Hsp70-Bag3 PPI, MKT-077 and an ATP-competitive inhibitor VER155008, were used as chemical tools. Cell viability assays, co-immunoprecipitation and gene knockdown were used to investigate the role of Hsp70 in tamoxifen resistance. A xenograft model was established in which tamoxifen-resistant breast cancer (MCF-7/TAM-R) cells maintained in the presence of 5 μM tamoxifen were subcutaneously inoculated. The anti-tumor efficiency of S1g-2 was measured after a daily injection of 0.8 mg/kg for 14 days. Results It was revealed that Hsp70-Bim PPI protects ERα-positive breast cancer from tamoxifen-induced apoptosis through binding and stabilizing ERα36, rather than ERα66, resulting in sustained EGFR mRNA and protein expression. Disruption of Hsp70-Bim PPI and downregulation of ERα36 expression in tumor samples are consistent with the in vitro functions of S1g-2, resulting in about a three-fold reduction in tumor volume. Conclusions The in vivo activity and safety of S1g-2 illustrated that it is a potential strategy for Hsp70-Bim disruption to overcome tamoxifen-resistant ER-positive breast cancer.